CREATIVITY AND INNOVATION IN TECHNOLOGY AND OPERATIONS MANAGEMENT THROUGH BRAINSTORMING - Ana Cruz Suarez; Juan-Gabriel Martínez-Navalón; Vera Gelashvili; Giovanni Herrera-Enríquez (Journal of Management and Business Education, 2022)
This research develops an exploratory study on the impact of brainstorming on students' creativity and innovation. Therefore, the purpose of this research study is to advance on: how much the creativity and innovation of students increases with the use of brainstorming; how contextual variables influence creativity and innovation when brainstorming is applied, and; how the legitimacy given by students to the brainstorming methodology influences the results achieved in creativity and innovation. The results show that the application of brainstorming, among a sample of 89 students of the technology and operations management course, leads to significant increases in creativity and innovation. They also show that there are no significant differences according to age, study background and gender. Finally, it demonstrates the importance of the degree of acceptability and desirability of brainstorming in the teaching and learning process to improve student outcomes. Having legitimacy is positive because it conveys confidence to students, encouraging learning. Future research could analyse the role of legitimacy of teaching methods on student outcomes.